2022
DOI: 10.1302/2046-3758.116.bjr-2021-0490.r1
|View full text |Cite
|
Sign up to set email alerts
|

Human acellular amniotic membrane scaffolds encapsulating juvenile cartilage fragments accelerate the repair of rabbit osteochondral defects

Abstract: Aims The purpose of this study was to explore a simple and effective method of preparing human acellular amniotic membrane (HAAM) scaffolds, and explore the effect of HAAM scaffolds with juvenile cartilage fragments (JCFs) on osteochondral defects. Methods HAAM scaffolds were constructed via trypsinization from fresh human amniotic membrane (HAM). The characteristics of the HAAM scaffolds were evaluated by haematoxylin and eosin (H&E) staining, picrosirius red staining, type II collagen immunostaining, Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…A recent study by Zhang et al demonstrated the feasibility of human acellular amniotic membrane (HAAM) scaffolds (Figure 3B). [38] They seeded third-generation (P3) human amniotic mesenchymal stem cells and juvenile cartilage fragments (JCFs) on it and placed the scaffolds in rabbits with osteochondral defects. The results showed that the HAAM scaffolds combined with JCFs promoted the repair of cartilage defects.…”
Section: Collagen and Gelatinmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Zhang et al demonstrated the feasibility of human acellular amniotic membrane (HAAM) scaffolds (Figure 3B). [38] They seeded third-generation (P3) human amniotic mesenchymal stem cells and juvenile cartilage fragments (JCFs) on it and placed the scaffolds in rabbits with osteochondral defects. The results showed that the HAAM scaffolds combined with JCFs promoted the repair of cartilage defects.…”
Section: Collagen and Gelatinmentioning
confidence: 99%
“…[ 26 ] Copyright 2021, Elsevier Inc. B) Schematic diagram of the fabrication of human acellular amniotic membrane scaffolds. [ 38 ] Reproduced with permission. [ 38 ] Copyright 2022, Bone & Joint Research.…”
Section: Terrestrial‐inspired Materials For Oamentioning
confidence: 99%
See 1 more Smart Citation
“…Several matrix-induced chondrogenic techniques have recently been developed and have demonstrated acceptable clinical results for medium-sized lesions. [5][6][7][8] These methods are potential strategies for treating medium-sized lesions via a single-step procedure. Alginate gels are biocompatible materials used to replace chondral defects and have demonstrated biochemical characteristics similar to native hyaline cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…AAM has been shown in some tests to lessen acute liver injury and speed bone repair. (Jun et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%